Development of Cefr-Based Qowā'id Learning Evaluation Tool with The Help of Wordwall Interactive Games to Identify Students' Understanding - Irfan Hania; R. Umi Baroroh; Madah Rahmatan; Alimudin Alimudin; Yuli Imawan (Arabic Education Program IAIN Pekalongan, 2022)
This development research aims to develop a qowā'id learning evaluation tool based on CEFR using the interactive game Wordwall with the intention of identifying the level of understanding of students and so that it can be accessed by students in a more flexible manner without limited space and time, more effectively and it is hoped that it will also be more effective in maintenance. This research is research development (Research & Development). This research aims to produce a product or develop a product. The results in this study show an average score of material experts of 85%, which means the product is considered feasible. very good, and 88% linguists which means the product is rated very good. While the results of student responses by distributing questionnaires obtained a score proportion of 91.19%, which means very good. As for the test results to measure the level of understanding of the qawā'id material of students using the interactive game Wordwall showed that 78.51% understood the material and 21.49% did not understand the material. From these results it can be seen that the proportion of students who understand the material and do not understand the material for each number is very diverse.